CONTROL ACTIONS FOR THE OBJECTS DESCRIBED BY DISCRIMINANT OR REGRESSION FUNCTIONS - Tatyana Valeryevna Kukharova; Elena Gavrilovna Papush; Ivan Mitrofanovich Pershin; Vladimir Aleksandrovich Utkin (Современная наука и инновации, 2022)
Either classifying functions or regression equations can serve as an analogue in the statistical research. We consider the possibility of defining the values of controlling actions which converse an object from the given state (with the given regression equation or with a set of classifying functions) to another state (which corresponds to another regression equation or another set of classifying functions) based on the statistical data of observations and experiments.